SARS-CoV-2 Threat Perception and Willingness to Vaccinate: The Mediating Role of Conspiracy Beliefs - Maftei, Alexandra; Holman, Andrei Corneliu (Frontiers in Psychology, 2021)
In the current exploratory study, we investigated participants' willingness to vaccinate against the novel coronavirus (SARS-CoV-2) that shook up the world since the beginning of 2020. More specifically, we tested the mediating role of conspiracy beliefs on the relationship between COVID-19 threat perception and participants' willingness to vaccinate, along with a series of associated demographic variables. Overall, 40% of our sample expressed total rejection of the COVID-19 vaccine. Our results suggested no significant differences in participants' gender, age, educational level, and vaccine acceptance or hesitancy. Results also indicated that conspiracy beliefs partially mediated the relationship between threat perception and participants' willingness to vaccinate. The current findings are discussed within the theory of planned behavior (TPB) framework and their importance for public health communication and practices and building public trust within the COVID-19 global fight. We consider the present results as a valuable starting point in understanding the psychological constructs related to the extended model of TPB and other personal factors and address the attitudinal roots that shape COVID-19 vaccination acceptance and rejection.